The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1021/ac060324r
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Folate Binding Protein with Enhanced Sensitivity Using a Functionalized Quartz Crystal Microbalance Sensor

Abstract: In this report, we describe the development of a quartz crystal microbalance biosensor for detection of folate binding protein (FBP). Using a simple folate-BSA conjugate adsorbed onto a Au-coated quartz sensor, a detection limit of 30 nM was achieved. Binding of FBP to the sensor surface could be blocked at concentrations as high as 1 microM with a 100-fold excess of folic acid, indicating the specificity of the folate-FBP interaction and the absence of nonspecific binding to the functionalized surface. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 35 publications
(86 reference statements)
0
48
0
Order By: Relevance
“…In an early report, Zhou and coworkers reported that nanoparticle amplification lowered the limit of detection for a target strand of DNA from 1.7 nM to 0.32 pM, a 100‐fold improvement 54. This approach has also been successful for the detection of proteins, such as the folate‐binding protein 55. Using the same type of sensor setup, Jiang and coworkers reported an even lower limit of detection for DNA of 10 fM 56.…”
Section: Electrical Detectionmentioning
confidence: 99%
“…In an early report, Zhou and coworkers reported that nanoparticle amplification lowered the limit of detection for a target strand of DNA from 1.7 nM to 0.32 pM, a 100‐fold improvement 54. This approach has also been successful for the detection of proteins, such as the folate‐binding protein 55. Using the same type of sensor setup, Jiang and coworkers reported an even lower limit of detection for DNA of 10 fM 56.…”
Section: Electrical Detectionmentioning
confidence: 99%
“…An interesting example of developing a protein surface to detect folate-binding protein (FBP) has been reported by Henne et al [43]. A gold surface was modified by immobilization of a folate-bovine serum albumin (BSA) conjugate which enabled the detection of FBP with a detection limit of 30 nM.…”
Section: Detection Of Proteinsmentioning
confidence: 99%
“…For more accurate and reliable diagnosis in disease state and widespread application, detection methodologies need to be accurate, sensitive, cheap, and easy to use, to facilitate rapid diagnosis, minimize sample decomposition, and decrease patient anxiety. To accomplish the task, many studies have been devoted to development of various signal transduction methods based on optics [1], radioactivity [2,3], fluorescence [4], electrochemistry [5], quartz crystal micro balance [6], piezoelectric cantilever [7], colorimetry [8,9], scanometry [10,11], surface plasmon resonance spectroscopy [12,13], etc. However, each of them still has its shortcomings such as necessitating time-consuming procedures, complicated manipulation and low sensitivity.…”
Section: Introductionmentioning
confidence: 99%